2021
DOI: 10.3390/ijerph18052317
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiorespiratory Fitness with Achievement Motivation in Physical Education in Adolescents

Abstract: Cardiorespiratory fitness is an important health marker in adolescents. Thus, examining the relation between cardiorespiratory fitness and motivation should be important to increase health-related behaviors. This study aimed to describe adolescents’ cardiorespiratory fitness and motivation by gender and to analyze the association between two cardiorespiratory fitness tests (original and with music) and motivation. A total of 341 adolescents (14.2 ± 1.5 years, 52.2% girls) participated in this study. Cardioresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The increasing importance of successful physical activity (PA) motives is unequivocal for a healthy lifestyle [ 1 ], mental and physical fitness [ 2 4 ], increased participation in organized and group-based PA [ 5 , 6 ], suitable climate for PA in physical education lessons [ 7 ], and children's and adolescents' well-being [ 8 , 9 ]. The number of interventions that use PA motives to support children's and adolescents' PA is similarly increasing [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing importance of successful physical activity (PA) motives is unequivocal for a healthy lifestyle [ 1 ], mental and physical fitness [ 2 4 ], increased participation in organized and group-based PA [ 5 , 6 ], suitable climate for PA in physical education lessons [ 7 ], and children's and adolescents' well-being [ 8 , 9 ]. The number of interventions that use PA motives to support children's and adolescents' PA is similarly increasing [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important as dance in music has been identified to contribute to enjoyment in performing a specific physical activity. To confirm this, Cadenas-Sanchez et al (2021) found that motivation was stronger when music is included in performing a cardiorespiratory fitness test. Therefore, performing practical lessons during physical education, music and dance may play a critical role in motivating learners to achieve their objectives.…”
Section: Discussionmentioning
confidence: 96%
“…More specifically, dance in music has been found to contribute to this enjoyment. For example, Cadenas-Sanchez et al (2021) in a study to examine the link between cardiorespiratory fitness and achievement motivation in Physical Education found that motivation was stronger when music is included in the test. The researchers concur that incorporating music into cardiorespiratory fitness activities could improve cardiorespiratory fitness performance and motivation, particularly in females.…”
Section: Introductionmentioning
confidence: 99%
“…Achievement motivation refers to the driving force of the individual pursuit of success as well as efforts and persistence in the face of challenges (Richter et al, 2021). Achievement motivation may be divided into two dimensions: motivation for success and motivation to avoid failure (Cadenas-Sanchez et al, 2021). Specifically, when an individual's behavior is dominated by the pursuit of success, it manifests as striving for progress and active efforts.…”
Section: Mediating Role Of Achievement Motivationmentioning
confidence: 99%